Bruton’s Tyrosine Kinase and Its Isoforms in Cancer - Wang, Xianhui; Kokabee, Leila; Kokabee, Mostafa; Conklin, Douglas S. (Frontiers in Cell and Developmental Biology, 2021)
Bruton’s tyrosine kinase (BTK) is a soluble tyrosine kinase with central roles in the development, maturation, and signaling of B cells. BTK has been found to regulate cell proliferation, survival, and migration in various B-cell malignancies. Targeting BTK with recently developed BTK inhibitors has been approved by the Food and Drug Administration (FDA) for the treatment of several hematological malignancies and has transformed the treatment of several B-cell malignancies. The roles that BTK plays in B cells have been appreciated for some time. Recent studies have established that BTK is expressed and plays pro-tumorigenic roles in several epithelial cancers. In this review, we focus on novel isoforms of the BTK protein expressed in epithelial cancers. We review recent work on the expression, function, and signaling of these isoforms and their value as potential therapeutic targets in epithelial tumors.